Contemporary computational mathematics: a celebration of the 80th birthday of Ian Sloan - Dick, Josef; Kuo, Frances Y.; Woźniakowski, Henryk (Springer, 2018)
Preface -- Family Perspectives -- A Fortunate Scientific Life -- Publications of Professor Sloan -- Contents -- Index
Keywords: Festschrift; Computermathematik